1994
DOI: 10.1575/1912/5577
|View full text |Cite
|
Sign up to set email alerts
|

Seismic constraints on shallow crustal processes at the East Pacific Rise

Abstract: This thesis is concerned with understanding how oceanic crust is emplaced at mid-ocean ridges. The emphasis is upon fast-spreading ridges, and the use of seismic techniques to image the uppermost several hundred meters of the crust. We present the results of nine on-bottom seismic refraction experiments carried out over young East Pacific Rise (EPR) crust. The experiments are unusual in that both the source and receiver are located within a few meters of the seafloor, allowing high-resolution determinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
(195 reference statements)
2
3
0
Order By: Relevance
“…On the basis of these observations we infer that off-axis magmatism along this section of the EPR affects the thickness of the volcanic section and perhaps the thermal structure of young oceanic crust. In particular, the variations in structure witlain 600 m of the seafloor support the view that off-axis volcanism has increased the thickness of layer 2A in the south and west of the study area, an interpretation also supported by the results of Harding et al [1993] and Christeson [1994]. The lower velocities observed to the west of the rise at 1-2 km depth are attributed to elevated temperatures resulting from either increased off-axis magmatism or a decrease in the efficiency of hydrothermal cooling.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…On the basis of these observations we infer that off-axis magmatism along this section of the EPR affects the thickness of the volcanic section and perhaps the thermal structure of young oceanic crust. In particular, the variations in structure witlain 600 m of the seafloor support the view that off-axis volcanism has increased the thickness of layer 2A in the south and west of the study area, an interpretation also supported by the results of Harding et al [1993] and Christeson [1994]. The lower velocities observed to the west of the rise at 1-2 km depth are attributed to elevated temperatures resulting from either increased off-axis magmatism or a decrease in the efficiency of hydrothermal cooling.…”
Section: Discussionsupporting
confidence: 75%
“…Under the premise that velocity anomalies within approximately 600 m of the seafloor are a result of variations in the thickness of the volcanic section, the tomographic results suggest that this extrusive layer thickens from north to south and from east to west. In support of this interpretation, Christeson [1994] reports that the thickness of layer 2A…”
Section: Interpretation and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Locally, between 17øS and 17ø30'S, Mutter et al [1995] report that the magma sill becomes shallower and wider as the ridge axis becomes shallower and broader and use deviations from this expected relationship to suggest very recent or ongoing magmatic activity near 17ø26'S. Seismic layer 2A in young oceanic crust is usually interpreted to be the volcanic extrusive section [e.g., Christeson, 1994;Hooft et al, 1996]. It has been suggested that the thickness of the seismic layer 2A reflects the magma budget [Harding et al, 1993].…”
supporting
confidence: 73%
“…Locally, between 17øS and 17ø30'S, Mutter et al [1995] report that the magma sill becomes shallower and wider as the ridge axis becomes shallower and broader and use deviations from this expected relationship to suggest very recent or ongoing magmatic activity near 17ø26'S. Seismic layer 2A in young oceanic crust is usually interpreted to be the volcanic extrusive section [e.g., Christeson, 1994 [Detrick et al, 1993] EPR that are not related to changes in the depth or cross-sectional area of the ridge. Lonsdale [1983Lonsdale [ , 1986Lonsdale [ , 1989a has questioned the correlation between segmentation of the magmatic system with that of the axial morphology and suggests that small overlapping spreading centers (OSCs) may be underlain by a single, wide crustal magma chamber.…”
Section: Introductionmentioning
confidence: 99%